Pengaruh Efektivitas Penerapan Sistem Informasi Akuntansi, Gaya Kepemimpinan dan Disiplin Kerja Terhadap Kinerja Karyawan Pada Lembaga Perkreditan Desa di Kota Denpasar - Ni Komang Sri Widari; Ni Luh Putu Ratna Wahyu Lestari (Universitas Warmadewa, 2026)
This research aims to identify the influence of the effectiveness of the implementation of SIA, leadership style and work discipline on employee performance. The population in the research is LPD employees in Denpasar City with the illustration used being 140 respondents. The information analysis method used in this research is Multiple Linear Regression. Based on the research results, it can be seen that: (1) the effectiveness of the implementation of the accounting data system has a good and significant impact, where a regression coefficient of 0.485 is obtained. (2) leadership style has an increasing and significant impact, obtaining a regression coefficient of 0.293. (3) work discipline has a good impact on employee performance, with a coefficient of 0.318. The recommendation that can be given is that LPD in Denpasar City can try to improve employee performance by increasing the effectiveness of the implementation of SIA, leadership style and work discipline.